(untitled) (Palíndromo, 2019)
What do we see in a photograph corresponds to reality? To be closer to an intimacy considered as credible it is possible due to selfie practice in recent years. However, what we see can be a performance of the daily life through the staged image (POIVERT, 2010) with spec-ificities of selfie (TIFENTALE, 2016) face of the (traditional) portrait. To exemplify this phenomenon with selfies an analysis is made of “Excellences and Perfections” by the artist Amalia Ulman who forges a narrative of her daily life through posts in the Instagram app. Through her work it is possible to elucidate how the (self)portrait/selfie can be ambiguous, putting the relationship between “real life” and the staged at stake.